Ethical reflections related to the use and research of nanotechnolog - Martel-Estrada, Santos-Adriana (2022)
Currently, nanotechnology is an emerging interdisciplinary knowledge area; this discipline encompasses biomedical food, energy, arms, and its industrial uses. Despite its applications’ potential, there is a need to ethically consider the benefits and risks that nanotechnology uses and development represent for natural, economic, and social ecosystems. This document analyzes ethical issues of nanotechnology use. Considering its bioethical dimensions, an analysis of the risk and regulatory aspects can be carried out. For these reasons, a reflection related to the ethical and bioethical implications of the different nanotechnological applications becomes relevant without neglecting their possible benefits and threats. In general, these reflections must drive researchers to influence the national and international regulatory framework, not to limit scientific progress. It also ensures that said progress does not threaten human beings’ safety and the planet in general